"It's Not Just a Bunch of Buildings": Social Psychological Investment, Sense of Community, and Collective Efficacy in a Multiethnic Low‐Income Neighborhood. (September 2016) - Walton, Emily
Abstract : This analysis of social life in a poor, multiethnic public housing neighborhood presents an opportunity for refinement of social disorganization theory. Drawing on data from interviews, focus groups, and participant observations among residents, I find that this neighborhood exhibits substantial collective efficacy, despite social disorganization theory's predictions that the structural conditions of high poverty and racial and ethnic diversity result in low collective efficacy. I explicate two social psychological investment strategies—sense of ownership and symbolic representation—that appear to facilitate a sense of community and ultimately collective efficacy, helping to explain this apparent anomaly. I argue that even in the presence of structural disadvantage, having a strong sense of community provides a basis for beneficial action on behalf of the collective because it constitutes a source of shared expectations about values and norms in the neighborhood. These findings suggest refinements to the social disorganization framework, but also provide foundational ideas for policy interventions that may improve the social lives of residents in disadvantaged neighborhoods.